Comparative analysis of processors performance using ANN - Maurya V.; Gupta S.C. (My University, 2025)
In the present era of plurality and diversity in electronic world taking decision for choosing the best one from a pool of products is a prudent approach. Machine learning helps us a lot in deciding the optimal choice. Artificial Neural Network are a family of statistical learning algorithms inspired by biological neural networks and can be incorporated to take a decision at par with a smart human perception. The purpose of this paper is to compare performance of CPU processors using some characteristics that are used as input, and subsequently comparing that result with existing performance that is published. © 2015 IEEE.